Pemahaman Siswa Kelas VIII SMP Melalui Media Pembelajaran Thunkable Pada Materi Momentum dan Impuls - Nikhlatul Maula; Wafiyah, Dzihni; Hikmah Mauliddy; Ziyanti Putri Setia Gandi (Jurnal Multidisiplin Indonesia, 2024)
Researchers will use thunkable mobile learning as a learning medium that will be developed to assist in the learning process. This research aims to analyze the effect of using thunkable media on class VIII SMP students in impulse momentum material. Knowing the role of learning media using thunkable applications, knowing the benefits of thunkable applications in impulse momentum material for class VIII SMP students. The method used in this research is the pre-post test method. Research design regarding how to collect, process and analyze data systematically. This type of research uses experimental research. The population in this study was five students in class VIII of junior high school. The test results of the five students using the Sprint Physics: Moi Quiz application increased on average, the data obtained had an average score achieved for the pretest with a maximum score of 35.7 and a minimum score obtained of 7.14. Meanwhile, the average score achieved for the post-test was a maximum score of 99.96 and a minimum score of 78.54.